Spermatogenesis in vitro: the future promise for azoospermia patients - Abdul Wahab, Azantee Yazmie; Ramli, Roszaman; Md Isa, Muhammad Lokman (2017)
Male inferti lity becomes a worldwide problem and contributed to 50% of infertility cases. The main cause of male inferti lity is spermatogenes is failure such as oligozoospermia and azoospermia. Azoospermia is defined as absence of spermatozoa from semen and it is related to incomplete spermatogenesis process which related to genetic disorder, hormonal problem or testicular failure. Recreating human spermatogenesis outside of its original environment is a scientific curiosity in andrology world and a quest for male fertility treatment. It has a huge impact on our understanding on ph) siology and pathway of genetic in male reproduction using a well-characterized model of human spermatogenesis. Animal studies have provided us the knowledge of gonadogenesis, spermatogenesis and steroidogenesis based on the histology, immunohistochemistry, hormonal assays and phenotype of gene alterations. In vitro spermatogenesis in azoospermic patients has long been attempted, however, it remains challenging due to limitation of cu lture system. Human embryonic stem cell (hESC) media were widely used for embryonic stem cell culture and some of these studies had derived the male germ cells from embryonic stem cells. This media could possible initiate the SSCs-like cell from adult testicu lar stem cells. The purpose of this study is to proliferate the SSCs-like cell and differentiate into next stage of spermatogenic cell using modified hESC media. Gene expressions were done to determine the spermatogenesis stages ach ieved.